Nanopackaging solution from clean room to UHV Environment: Hydrogen Passivated Si (100) Substrate Fabrication and Use for Atomic Scale Investigations and Self-Assembled Monolayer Grafting. (2016) - Reynaud, P.; Thuaire, A.; Sordes, D.; Rauer, C.; Hartmann, J.M.; Moriceau, H.; Bhartia, B.; Puniredd, S.R.; Troadec, C.; Srinivasan, M.P.; Baillin, X.; Cheramy, S.
Abstract: Specific surfaces allowing Ultra-High Vacuum (UHV) investigations are required for the successful development of atomic nanostructures. Surface contamination, atomic roughness and defects density must be controlled in order to ensure the reliability of advanced UHV experiments. Surface preparation is a key parameter and is usually conducted in-situ in the UHV chamber. However the surface preparation requires a complex protocol. A microelectronic clean room environment enables the particles density control and enables 200 mm wafer scale developments, especially Si(001)-(2x1):H surface reconstruction. However, this passivated surface is reactive and can be easily deteriorated, particularly during transportation. Consequently, a nanopackaging solution is proposed in order to provide a preserving environment for transportation. The nanopackaging process consists in the direct bonding of two passivated silicon surfaces, and is followed by a wafer dicing step into 1cm 2 dies. Samples can be stored, shipped and in-situ opened without additional treatment. Furthermore, these samples can provide a reliable surface onto which molecular grafting can be accomplished. The fabrication modules and the associated characterization results will be described as well as atomic nanostructure manipulations and especially the grafting of a self-assembled monolayer using supercritical carbon dioxide as a medium.